2016
DOI: 10.21873/anticanres.11110
|View full text |Cite
|
Sign up to set email alerts
|

What Characterizes Long-term Survivors of Recurrent Ovarian Cancer? Case Report and Review of the Literature

Abstract: LTSROC are rare, with 360 cases described in the literature. LTSROC are characterized by young age, low tumor stage, long recurrence-free interval and combined modality treatment with optimal cytoreductive surgery and systemic chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…However, this data was not available in the present study as the analysis was retrospective. In the recurrent setting, similar results were reported with age [7] being associated with long-term survival. Another study of recurrent platinum-sensitive patients found a that over half of patients survived more than 5 years (52.8%) [36].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, this data was not available in the present study as the analysis was retrospective. In the recurrent setting, similar results were reported with age [7] being associated with long-term survival. Another study of recurrent platinum-sensitive patients found a that over half of patients survived more than 5 years (52.8%) [36].…”
Section: Discussionsupporting
confidence: 81%
“…Another study of recurrent platinum-sensitive patients found a that over half of patients survived more than 5 years (52.8%) [36]. Multimodal treatment was also associated with long-term survival in different studies [7,37,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, in that study, 14% of the long‐term survivors had suboptimal RD, 11% had short platinum‐free intervals (<12 months), and 53% had recurrent disease. Hilal et al . also reported the characteristics of 360 cases of long‐term survivors of recurrent ovarian cancer through a PubMed literature search.…”
Section: Discussionsupporting
confidence: 71%
“…Regarding factors influencing the survival of patients, one study revealed that prolonged post progression survival of recurrent ovarian cancer patients was associated with post recurrence treatment, including secondary debulking surgery, favorable response to second-line therapy, and more than two chemotherapy regimens after the first recurrence (Soyama et al, 2017). Hilal (2016) reported that long-term survival of recurrent ovarian cancer was characterized by a young age, low tumor stage, long recurrence-free interval, and combined modality treatment with optimal cytoreductive surgery and systemic chemotherapy. Multiple retrospective…”
Section: Discussionmentioning
confidence: 99%